PENGARUH MANAJEMEN SALURAN PEMASARAN TERHADAP PENGETAHUAN KONSUMEN BISNIS PT. SARI HUSADA, TbK. CABANG BANDUNG - Hetty Karunia Tunjungsari (Jurnal Manajemen., 2007)
A research at PT Sari Husada, Tbk. Bandung Branch Office was done to find the influence of channel management practice (selection, motivation, evaluation,modification) on consumers knowledge (selection process, motivation process, evaluation process, and modification process). A sampel of 50 gynaechologists and nurses (bidan) were taken to fill in the researchs questionnaires. From the hypothesis test it was found that HO is accepted, that is, there is no significan influence of channel management practice (motivation) on consumers knowledge. That means that the relationship between channel management ... practice (motivation) and consumers knowledge is not strong enough. From this research regression equations can not be derived to represent a research model, because whether in general or. individually there are no significant influence of channel management practice on consumers knowledge.